Subacute and Chronic Effects of DDD Pacing on Left Ventricular Diastolic Function in Patients With Non-Obstructive Hypertrophic Cardiomyopathy - Sueda, Shozo; Watanabe, Kouki; Ikeda, Shuntaroh; Tsuruoka, Takashi; Suzuki, Jun; Sekiya, Michihito; Funada, Jun-ichi (JAPANESE CIRCULATION JOURNAL, 2001)
The present study examined the ability of dual-chamber (DDD) pacing to improve symptoms and exercise tolerance in patients with non-obstructive hypertrophic cardiomyopathy (HNCM). Seven patients with HNCM who had failed to benefit from pharmacotherapy participated in the study. The New York Heart Association (NHYA) functional class status and exercise tolerance, which was determined by the treadmill exercise test, were recorded and an echocardiographic observation was performed before, and 1 week, 3 months and 1 year after the implantation of a permanent DDD pacemaker. The atrioventricular delay (AVd) was determined by measuring the point of peak rapid filling velocity and maximum cardiac output (CO). Two patients were not implanted with a permanent pacemaker because their CO and blood pressure decreased or because palpitation occurred during temporary pacing. The ratio between early and late peaks of flow velocity (1.56, 1.21, 0.95, and 0.86 before implantation and 1 week, 3 months and 1 year after implantation, respectively); deceleration time (ms: 263.2, 217.6, 204.6, 187.0); peak filling rate (ml/s: 146.2, 204.0, 233.2, 243.6); NYHA functional class status (2.0, 1.8, 1.6, 1.4); and exercise tolerance (s: 203, 264, 403, 480) were significantly improved after implantation. However, left ventricular dimension, percent fractional shortening, ejection fraction, acceleration time and the isovolumic relaxation time were not changed significantly. In conclusion, DDD pacing improved symptoms and the NYHA functional class status, which is associated with improvement of left ventricular diastolic function. It is proposed that DDD pacing would be useful in patients not only with obstructive but also non-obstructive hypertrophic cardiomyopathy refractory to medical treatment, depending on the careful selection of subjects. (Jpn Circ J 2001; 65: 283 - 288)